Application of rock hardness and abrasive indexing to rock excavating equipment selection - Cassapi, V.B. (1987)
The work carried out in this thesis outlines some of the problems associated with abrasive wear in machines and other mechanical equipment used to excavate or process natural rock material. It has been stated that if the problems associated with abrasion are to be better understood, then a sound knowledge of the abrasive potential of rocks is essential. A number of common wear mechanisms are described together with existing hardness and abrasive tests.